2018
DOI: 10.1007/s10068-017-0286-9
|View full text |Cite
|
Sign up to set email alerts
|

Multiplex PCR assay and lyophilization for detection of Salmonella spp., Staphylococcus aureus and Bacillus cereus in pork products

Abstract: Multiplex PCR (m-PCR) has the potential for more rapid detection of pathogens compared to simple PCR through the simultaneous amplification of multiple gene targets using several sets of specific primers. Here, we developed an m-PCR assay which combined dry reagent mixtures for ready-to-use simultaneous detection of spp.,, and . The assay did not show cross-reactivity with several common bacterial pathogens and the detection limit was 10 CFU/mL for mixed genomic DNA in pure culture. Lyophilized m-PCR reagents … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
9
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
7
1
1

Relationship

1
8

Authors

Journals

citations
Cited by 26 publications
(10 citation statements)
references
References 20 publications
1
9
0
Order By: Relevance
“…Furthermore, it has also been reported that gene62181533 amplification can be effectively used to specifically detect the contamination of pork products by Salmonella spp. without cross‐reacting with several other common bacteria (Arunrut et al, ). Thus, based on our results and previous findings, it can be established that gene62181533 is a suitable target gene for the direct detection of Salmonella in biological samples.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Furthermore, it has also been reported that gene62181533 amplification can be effectively used to specifically detect the contamination of pork products by Salmonella spp. without cross‐reacting with several other common bacteria (Arunrut et al, ). Thus, based on our results and previous findings, it can be established that gene62181533 is a suitable target gene for the direct detection of Salmonella in biological samples.…”
Section: Discussionmentioning
confidence: 99%
“…Generally, detection and identification of Salmonella spp. is performed by conventional culture methods that are both timeconsuming and labor-intensive, with a minimum of 5 days required to complete the analysis (Ananchaipattana, Bari, & Inatsu, 2016;Arunrut, Kiatpathomchai, & Ananchaipattana, 2018). Immunological assays require less time but provide poor specificity with high rates of false positives.…”
mentioning
confidence: 99%
“…Several publications on freeze-dried PCR mixes have been reported during the past 20 years ( Table S1 ) [ [9] , [10] , [11] , [12] , [13] , [14] , [15] , [16] , [17] , [18] , [19] , [20] , [21] ]. In previous studies, electrophoresis has frequently been used to evaluate the activities of freeze-dried PCR reagents [ 9 , 10 , 12 ].…”
Section: Introductionmentioning
confidence: 99%
“…However, lyophilisation process is costly and requires the addition of excipients, such as cryoprotectants and bulking agents. 17,19…”
Section: Introductionmentioning
confidence: 99%